MODERN METHODS IN THE STUDY OF NOMINATIVE SENTENCES IN THE LANGUAGE SYSTEM - Azamova Dilafruz Bakhodirovna (Galaxy International Interdisciplinary Research Journal, 2022)
In modern linguistics, there are several different methods of researching nominative sentences in the language system. Currently, there are several types of these methods. The article discusses the methods used by American descriptive linguistics in the inventory of the grammatical level .